The Effect of Labor, Private Investment and Government Investment on Productivity in the Industrial Sector - E. Elpisah; Nurmiati Irvan; Muh. Yahya; Andi Annisa Sulolipu; Amnah Hadi (International Journal of Artificial Intelligence Research, 2022)
This research was conducted with the objectives of 1) to determine the effect of labor on production in the industrial sector in Sidenreng Rappang Regency; 2) to determine the effect of private investment on production in the industrial sector in Sidenreng Rappang Regency; 3) to determine the effect of government investment on production in the industrial sector in Sidenreng Rappang Regency. This research was carried out in Sidenreng Rappang Regency, starting from November 2021 to January 2022. Data collection was carried out at the Regional Financial Management Agency Office, the Sidenreng Rappang Regency Trade Office, the internet, and various agencies refining research data. The data used in this study is secondary data, namely data on the number of workers, private investment, and government investment. As well as data on the amount of production in the industrial sector within ten years (2012 - 2021) is analyzed and processed by the multiple linear regression method, using the SPSS version 22 program. The results of this study indicate that: (1) labor has a positive and significant influence on production in the industrial sector; (2) private investment has a positive and significant impact on production in the industrial sector; (3) government investment has a positive and significant impact on production in the industrial sector. This shows that production activities in the industrial sector in Sidenreng Rappang Regency rely on labor, private investment, and government investment to continue to increase production capacity.